Consistency of an adjusted least-squares estimator in a vector linear model with measurement errors - Sen'ko, I. O. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider the vector linear errors-in-variables model. For this model, we construct an adjusted least-squares estimator and prove its weak and strong consistency under various assumptions about measurement errors.